Implementation of Progressivism Philosophy to Develop 22nd Century Teacher Skills - Uswah, Atiq Yuftriyah; ramadhan, firman aullia; Wahono, Suparwoto Sapto; Machfudi, Moch Imam (IJIT: Indonesian Journal of Islamic Teaching, 2022)
Rapid changes must be balanced with human capacities in order to avoid errors in response, notably in the area of education. Errors in responding to it, including in the realm of education Education is crucial in developing human skills in the twenty-first century. The job of educational agents, in this case lecturers, must be aimed at producing potential educators who meet the standards and competencies sought in the twenty-first century. skills as sought in the twenty-first century This study employs library research to investigate data and information gathered from books, journals, papers, documents, notes, and other sources. The goal of this library research is to use the concept of progressivism philosophy in 21st century learning, particularly for future educators. The study's findings revealed which principles should be developed in library research, both theoretically and practically. both theoretically and practically, including elements that lecturers must develop, such as pedagogical competency and 21st century learning qualities, particularly for future educators incorporate pedagogical expertise and 21st century learning traits Furthermore, instructors must be capable of developing 4C thinking in students (critical thinking, creativity, collaboration, and communication). Prospective educators are provided with competencies that will subsequently be produced for pupils in accordance with the times under the current conditions. students in accordance with the times According to the notion of live long education (lifelong education), education must adapt to changing conditions. emphasizes the importance of adapting education to changing times